Palliative Care Team Involvement in Patients With COVID-19 in New York City. (October 2020) - Obata, Reiichiro; Maeda, Tetsuro; Rizk, Dahlia; Kuno, Toshiki
Background: With the highest number of cases in the world as of April 13, 2020, New York City (NYC) became the epicenter of the global coronavirus disease 2019 (COVID-19) pandemic. The data regarding palliative team involvement in patients with COVID-19, however, remains scarce. We aimed to investigate outcomes of palliative team involvement for the patients with COVID-19 in NYC. Methods: Consecutive 225 patients with confirmed COVID-19 requiring hospitalization in our urban academic medical center in NYC were analyzed. Patients were divided into 2 groups, those with a palliative care consult (palliative group: 14.2% [n = 32]) versus those with no palliative care consult (no palliative group: 85.8% [n = 193]). Results: The palliative group was older and had more comorbidities. During the hospital course, the palliative group had more intensive care unit stays, rapid response team activations, and more use of vasopressors ( P < .05). Patients with palliative care had higher rates of invasive mechanical ventilation than those without (46.9% vs 10.4%, P < .001). Cardiopulmonary resuscitation was performed in 12 patients (6.5% vs 5.2%, P = .77) and death rate was 100% in both subsets. Notably, initial code status was not different between the 2 groups, however, code status at discharge was significantly different between them ( P < .001). The rate of full code decreased by 70% in the palliative group and by 47.5% in the no palliative care group from admission to the time of death. Conclusions: Critically ill patients hospitalized for COVID-19 benefit from palliative team consults by helping to clarify advanced directives and minimize futile resuscitative efforts.